Network function virtualization elastic technology - Lu LIU; Zhibin GUO (Dianxin kexue)
According to NFV ETSI standard architecture，NFV system mainly includes NFVI，VNF and MANO three function modules and sub function modules.NFV elastic technology was analyzed，and it was emphasized that the flexible goal of network virtualization was mainly to ensure the continuity of the business，application design and virtualization facilities were also affected by this goal.And the principle of elastic structure design was summarized.